Does Africa’s Industrialization Foster Sustainable Emission Decoupled Economic Growth? The Case of Zambia and South Africa - Nsakaza, Kalimanshi; Simuchimba, Joshua; Banda, Evelyn (Cattleya Darmaya Fortuna, 2024)
In fostering sustainable growth for many developing nations, there is an urgent need to re-engineer the industrial sector towards one that promotes value addition, particularly on the industrial base. Zambia and South Africa’s major economic challenges revolve around their persistent economic dependence on copper and gold. Within the context of their broader goals to diversify their economies, Zambia has struggled to reduce its reliance on copper despite various initiatives, while South Africa faces declining gold production and the need to adapt to global sustainability trends and changing resource demands. Using a dynamic Panel ARDL model, this study thus analysed the effects of industrialization on sustainable emission decoupled economic growth using data from 1970-2022 for South Africa and Zambia. Our results showed that the metallic, food and beverages, paper, and wood products industries significantly affected emission decoupled economic growth in South Africa, while only the fabricated metal and wood industry significantly fostered economic growth in Zambia in the short run. In the long run, for both countries, only the paper and non-metallic industries affected economic growth significantly. The study concluded that while extractive and high emitting industrial sectors are the most feasible in the case of most African countries; to be able to accelerate sustainable economic growth through the industrial sector, these nations will have to re-engineer their industrial sectors towards a more commodity-aligned approach that puts value addition and emission reduction through regional value chains at the pinnacle of policy and national development strategies.